2021
DOI: 10.1177/2167702621993900
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cardiovascular Reactivity Is Associated With More Childhood Adversity and Poorer Midlife Health: Replicated Findings From the Dunedin and MIDUS Cohorts

Abstract: Cardiovascular reactivity has been proposed as a biomarker linking childhood adversity and poorer health. In the current study, we examined the association of childhood adversity, cardiovascular reactivity, and health in the Dunedin Multidisciplinary Health and Development Study ( n = 922) and Midlife in the United States (MIDUS) studies ( n = 1,015). In both studies, participants who experienced more childhood adversity had lower cardiovascular reactivity. In addition, people with lower cardiovascular reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…The existing literature examining stressful life events, early childhood adversity, and trauma highlights the importance of investigating how study participants' characteristics and experiences might interact with different tasks to explain reactivity in the laboratory. Early life adversity and trauma are associated with lower levels of physiological reactivity across of a number of studies (Bourassa, Moffitt, et al, 2021;Ginty et al, 2017;McLaughlin et al, 2014McLaughlin et al, , 2015Murali & Chen, 2005;Voellmin et al, 2015). Experiencing early life adversity is theorized to result in a "freezing response" to general stress that could explain such findings (McLaughlin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The existing literature examining stressful life events, early childhood adversity, and trauma highlights the importance of investigating how study participants' characteristics and experiences might interact with different tasks to explain reactivity in the laboratory. Early life adversity and trauma are associated with lower levels of physiological reactivity across of a number of studies (Bourassa, Moffitt, et al, 2021;Ginty et al, 2017;McLaughlin et al, 2014McLaughlin et al, , 2015Murali & Chen, 2005;Voellmin et al, 2015). Experiencing early life adversity is theorized to result in a "freezing response" to general stress that could explain such findings (McLaughlin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for reconciling these differences is the need to better account for the types of tasks used to assess cardiovascular reactivity in the context of trauma or adversity. Many studies have found that early child adversity is associated with lower reactivity to cognitive and/or performative stressors (Bourassa, Moffitt, et al, 2021;Ginty et al, 2017;McLaughlin et al, 2014McLaughlin et al, , 2015Murali & Chen, 2005;Voellmin et al, 2015). Studies of trauma and PTSD in adults, in contrast, often use trauma-recall tasks to elicit reactivity (Bourassa et al, 2016;Bourassa, Moffitt, et al, 2021;Park et al, 2017;Pole, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations